Classification of Simply-Transitive Levi Non-Degenerate Hypersurfaces in ℂ3. (24th June 2021) - Doubrov, Boris; Merker, Joël; The, Dennis
Abstract: Holomorphically homogeneous Cauchy–Riemann (CR) real hypersurfaces M^3 C^2 were classified by Élie Cartan in 1932. In the next dimension, we complete the classification of simply-transitive Levi non-degenerate hypersurfaces M^5 C^3 using a novel Lie algebraic approach independent of any earlier classifications of abstract Lie algebras. Central to our approach is a new coordinate-free formula for the fundamental (complexified) quartic tensor. Our final result has a unique (Levi-indefinite) non-tubular model, for which we demonstrate geometric relations to planar equi-affine geometry.